Bradykinin measurement by liquid chromatography tandem mass spectrometry in subjects with hereditary angioedema enhanced by cold activation - Jinguo Chen, MD; Yunkou Wu, PhD; J. Joanna Yu, MD, PhD; Joseph Chiao, MD; Jing Yu, PhD; Mark D. Scarupa, MD; Lili Wan, PhD; H. Henry Li, MD, PhD (Journal of Allergy and Clinical Immunology: Global)
Background: Bradykinin (BK), a 9–amino acid peptide, is a key mediator responsible for angioedema attacks in hereditary angioedema due to C1INH deficiency (HAE-C1INH). Current BK assays lack clinical utility due to the instability of BK (half-life < 30 seconds) and low pg/mL baseline levels. Objective: We sought to develop a novel method to overcome the issues in current protease inhibitor–based methods for measuring endogenous BK. Methods: Blood samples from subjects with HAE-C1INH and healthy volunteers were collected and subjected to cold activation for the contact system. Cold-induced BK was measured via LC-MS/MS. The protocol was developed and validated according to the US Food and Drug Administration Bioanalytical Method Validation guidelines. The procedure was optimized on specimen selection, collection, and process, as well as variable controls such as time windows, temperature, and storage conditions. Results: EDTA whole blood samples without protease inhibitor were incubated at 4°C for 1 and 3 days. Total BK levels increased more than 100-fold in attack-free HAE-C1INH subjects compared with healthy volunteers (324.3 ± 54.7 ng/mL [n = 33] vs 2.3 ± 0.3 ng/mL [n = 43]; mean ± SEM, P < .001). The diagnostic sensitivity and specificity were 90.9% and 97.1%, respectively. BK levels highly correlated with plasma kallikrein activity in the same samples. Conclusions: Whole blood under cold activation showed striking elevation of BK levels in subjects with HAE-C1INH, while minimally affecting healthy volunteers. The assay has been assessed for accuracy, precision and stability. It may serve as a reliable tool for HAE diagnosis and management.